FIQH SOSIO-KULTURAL: INTERKONEKSI ANTARA PERADABAN TEKS DAN PERUBAHAN KONTEKS - Fathorrahman, Fathorrahman (Al-Mazaahib: Jurnal Perbandingan Hukum, 2012)
To understand and explain the building of Islamic law (fiqh) should not be fixated on the traditional topics of fiqh evolved in an sich. But as enrichment in fiqh useable insights such as the social sciences. Socio-cultural fiqh is a paradigm that try to combine between the fiqh that tend to normative and socio-cultural regions that lot to empirically grounded. This kind of fiqh is important to analyze the various fiqh issues when dealing with social realities and problems of society has changed, so, building Islamic law contains norms and worldview-that developed in the community can be appreciated as a process of strengthening and enrichment of fiqh in the modern era. It is, as is done by many previous muslim scholars of fiqh that also incorporate elements of socio-cultural as a means for determining the direction and the view of Islamic law. This paper tries to analyze deeper socio-cultural significance of fiqh as a means to develop the study of fiqh (tsarwah al fiqhiyah). At least, through this paper, we want to describe how the socio-cultural theory of fiqh in response to people's habits, one side needs related to the text and on the other hand it can not be separated from the context.